L'union homosexuelle et le droit de la famille - Deleury, Édith (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
Homosexuals have asserted their rights more vocally in many areas of the law in the past decade. It was inevitable that the area of family law and child custody would be affected by this trend. In this paper, the author tries to compare and assess the moral standards which govern family relationships and how those standards are reflected in the laws relating to marriage, divorce and appreciation by the courts of parental fitness.